2010
DOI: 10.1590/s1679-87592010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Status of the population structure of the mangrove crab Ucides cordatus (Decapoda: Ocypodidae) on the Piraquê-açu River estuary, Espírito Santo, Brazil

Abstract: The land crab Ucides cordatus is a keystone species of neotropical mangrove forests and an important resource of the artisanal fisheries. The spatial and temporal distribution of U. cordatus in the mangrove area of the Piraquê-açu river estuary was determined following a longitudinal estuarine salinity gradient (lower, middle, upper estuary) and along the vertical intertidal gradient. The numbers of open and closed burrows were counted monthly on fixed transects, the inhabiting crabs were caught, sexed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
2
12
0
2
Order By: Relevance
“…The present study also recorded similar founds to Conti et al (2010), since in the site 6 was recorded the highest frequency of small crabs (juvenile) at high density (Table 1, Figure 4).…”
Section: Population Structuresupporting
confidence: 89%
See 3 more Smart Citations
“…The present study also recorded similar founds to Conti et al (2010), since in the site 6 was recorded the highest frequency of small crabs (juvenile) at high density (Table 1, Figure 4).…”
Section: Population Structuresupporting
confidence: 89%
“…In this type of habitat, large crabs apparently exclude smaller ones from preferred habitats , thus favoring the dominance of the largest crabs. Conti et al (2010) found that highest crab density is linked to high numbers of juvenile crabs, which was found on the upper estuary and correlated with lower salinities .…”
Section: Population Structurementioning
confidence: 92%
See 2 more Smart Citations
“…Male-biased selectivity in exploited species such as U. cordatus can also change the sex ratio (Fenberg & Roy, 2007). According to Diele et al (2005), areas with a longer history of exploitation have a higher proportion of females, and this deviation may indicate that the population has been overfished (Conti & Nalesso, 2010;Sforza et al, 2010). The results obtained here suggest no evidence of overexploitation.…”
Section: Discussionmentioning
confidence: 54%